Social Dominance Orientation (SDO) and Political In(tolerance) among Islamists in Jakarta - Suryana, A'an; Alviano, Ismail; Ruchma Algiffary, Ghulam; Arisandi, Bobi (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2024)
Political intolerance—the unwillingness to accept the political freedom of those with differing views—has become an increasingly significant issue in Indonesia in recent years. The country began holding free and fair elections at the national level in 2004, with regional elections following shortly thereafter. Despite this progress, at least two surveys show that the level of political intolerance in Indonesia increased over time, peaking between 2017 and 2019. Several scholars have examined this issue in Indonesia through various perspectives, including online political intolerance. Others used the Social Dominance Orientation (SDO) method to measure the level of intolerance among particular groups. This research aims to expand the scholarship on political intolerance by examining the SDO levels among Islamists in Greater Jakarta, and whether the SDO levels positively correlate with their political intolerance. Using an explanatory approach with quantitative statistical analysis and qualitative in-depth interviews, this study examines the relationship between SDO levels and political intolerance. This study involves 265 Islamists in the Greater Jakarta region. The findings show that there is a positive correlation between the SDO levels and political intolerance, confirming the findings of previous studies that political intolerance usually parallels, and is built up by, higher levels of SDO among individuals. This is the first large study to investigate the level of SDO among Islamists in Jakarta.